Merit Pay and Social Work - Ursula H. Werling (Social Work and Society, 2011)
An economization of many social fields in Germany and other countries is under way, such as in the arts, journalism, education and science. Economic considerations have the upper hand in academic education (e.g., the introduction of tuition fees), while private co-payments have to be made for medical services (Schimank/Volkmann 2008, 382ff.).